Análisis del uso de las redes sociales como medio de interacción de las instituciones educativas “Padre Jorge Abiatar Quevedo Figueroa” y Unidad Educativa “Gonzanamá” con su público externo en la ciudad de Gonzanamá. Periodo abril- julio de 2020. - Quito Pinta, Nataly Silvana (2021)
This research focuses its study on the Educational Unit "Padre Jorge Abiatar Quevedo Figueroa" and the Educational Unit "Gonzanamá". The general objective is focused on analyzing the management that both establishments give to social networks and the interaction generated from them with their external public, in the period April - July 2020. For this, an interview was conducted with the people in charge of managing social networks, surveys were conducted with the parents of both educational institutions, in addition, observation sheets were prepared, from which information was collected taking into account aspects such as: No. of words, No. of comments, No. of tags, No. of reactions, Hashtags, etc. From these variables it was possible to identify the interaction generated by each publication. The research shows that the management of social networks by both educational establishments in the city of Gonzanamá is not adequate, because each publication issued in their institutional accounts does not have strategic messages, the contents are not visually attractive and there is no periodicity in each publication, which generates that the interaction between users and the institution is low. Given the various shortcomings that exist in the management of social networks of both educational institutions, a manual of use and style of social networks is presented as a proposal, which will allow these educational institutions to create and disseminate content according to the interests of their external audience, and thus, generate greater interaction.